2018
DOI: 10.3928/19382359-20180425-02
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Intestinal Obstruction Syndrome

Abstract: Neonatal intestinal obstruction is caused by an anatomical abnormality that produces bowel movement failure. Intestinal obstruction presents with three classic clinical signs: vomiting, abdominal distention, and failure to pass meconium. Intestinal obstruction is one of the most common causes for admitting a pediatric patient to the pediatric surgery unit in his or her first weeks of postnatal life. Congenital obstruction of the digestive tract in neonates is a common problem, with the most frequent cause bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 7 publications
0
12
0
3
Order By: Relevance
“…Further it has been also observed that using oral non absorbable antibiotics with parenteral antibiotics reduced the surgical site infection by 43%. 9 Nutritional status of individual is another key factor for successful anastomosis. Many studies show that prolonged and shortterm malnutrition decreases anastomotic healing.…”
mentioning
confidence: 99%
“…Further it has been also observed that using oral non absorbable antibiotics with parenteral antibiotics reduced the surgical site infection by 43%. 9 Nutritional status of individual is another key factor for successful anastomosis. Many studies show that prolonged and shortterm malnutrition decreases anastomotic healing.…”
mentioning
confidence: 99%
“…Jejunal duplication cysts frequently present neonatally or before two years of age [ 8 ]. The most common clinical presentations of jejunal duplication cysts include signs and symptoms of small bowel obstruction, including vomiting, abdominal pain, bloating, constipation, and abdominal masses [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cystic nontubular jejunal duplication cysts represent an exceedingly rare subset of these duplication cysts [ 3 , 4 ]. Clinically, jejunal duplication cysts present with a vague constellation of symptoms, including bilious vomiting, abdominal pain, bloating, and constipation, alluding to an underlying small bowel obstruction [ 5 ]. Here, we chronicle the case of a two-month-old girl who presented with a two-day history of bilious vomiting, constipation, and abdominal distension.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal polyhydramnios may suggest upper bowel obstruction. Upper and lower gastrointestinal tract contrast studies may be required in some cases [7]. Management of NIO is multidisciplinary.…”
Section: Introductionmentioning
confidence: 99%
“…Management of NIO is multidisciplinary. There is need for joint collaboration between the obstetrician at the time of prenatal diagnosis, the pediatrician that accepts the newborn in the delivery room, and the pediatric surgeon, who will determine the treatment according to the etiology [7]. Early diagnosis, prompt diagnosis and appropriate treatment have improved the outcome of NIO.…”
Section: Introductionmentioning
confidence: 99%